COMPARATIVE TYPOLOGICAL STUDY OF THE CHARACTERS IN THE STORIES OF ABDULLA QAHHOR AND ERNEST HEMINGWAY - Mirzaiyeva Nargiza Rajabboyevna (Journals Park Publishing, 2024)
This research focuses on the comparative typological study of the characters in the stories of Abdulla Qahhor, a prominent Uzbek writer, and Ernest Hemingway, a renowned American author. By analyzing the similarities and differences in the depiction of their characters, the study aims to explore how each writer reflects the socio-cultural and psychological aspects of their time. The research delves into the narrative techniques, the portrayal of human nature, and the thematic concerns in the works of both authors, offering insights into their unique literary styles and the influence of their respective historical and cultural backgrounds on character development.
Keywords: Abdulla Qahhor, Ernest Hemingway, comparative literature, typological study, character analysis, narrative techniques, Uzbek literature, American literature, socio-cultural context, psychological portrayal.